Fabrication of superhydrophobic-superoleophilic copper mesh via thermal oxidation and its application in oil–water separation - Yanlong, Shi; Wu, Yang; Xiaojuan, Feng; Yongsheng, Wang; Guoren, Yue; Shuping, Jin (Applied surface science, 2016)
•Copper mesh with superhydrophobicity and superoleophilicity was fabricated.•The mesh exhibited low adhesive self-cleaning and striking loading capacity.•The copper mesh could be applied to separate oil–water mixture.•The superhydrophobic copper mesh exhibits superior corrosion resistance. A copper mesh with superhydrophobicity and superoleophilicity was fabricated via thermal oxidation and subsequent surface modification. After surface treatment, the copper mesh exhibited self-cleaning properties, striking loading capacities, and superior anticorrosion. In addition, the copper mesh could be used in a separator for separating oil from oily water with high efficiency. The presented approach may provide a promising strategy for the design and construction of superhydrophobic-superoleophilic materials which can be used for separating oil from oily water.